The Development of Preksuya as a Learning Media of Integrated Science and Social Studies in Elementary Schools - Nabilla, Hana Safitri; Sukriadi; Mustamiroh (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study is grounded in the limited use of instructional media in the current era of rapidly advancing technology, which offers significant potential to support the learning process. One such thing that can be utilized is Prezi. The objectives of this research are: (1) to examine the development process of Preksuya as a learning medium for IPAS (Integrated Science and Social Studies) on the topic of social and cultural diversity in Indonesia for Grade IV students at SD Negeri 004 Sungai Kunjang; (2) to assess the feasibility of Preksuya as a learning medium for the same subject and grade level; and (3) to evaluate the practicality of Preksuya in the learning process. This research employs a Research and Development (R&D) methodology using the ADDIE model. The study subjects include a fourth-grade teacher and 22 students from SD Negeri 004 Sungai Kunjang. The outcome of the study is the development of Preksuya (Prezi for Ethnic and Cultural Diversity) as a learning medium for IPAS on the topic of social and cultural diversity in Indonesia. The feasibility test conducted by experts yielded a score of 89.6%, categorized as “Highly Feasible,” indicating the medium is appropriate for implementation in the classroom. Furthermore, the practicality test based on responses from the teacher and students resulted in a score of 92.2%, indicating that Preksuya is considered “Highly Practical” for use in the learning process.